Improving Literacy Skills through Letter Ball Games for Children 5-6 Years Old - Intan Wahyuni, Sri; Citra Dewi, Ayu; Nursaadah, Nursaadah (Indonesian Journal of Early Childhood Educational Research (IJECER), 2022)
Literacy skills is an indicator of language development that must be possessed by early childhood. The literacy skills of children in TKIT Champion are still low, such as children who are not yet able to read their own names, find it difficult to distinguish between several letters. Through the letter ball game it is hoped that it can improve the literacy skills of group B children at TK IT Champion. This research is a class action research. The subjects in this study were children aged 5-6 years in group B class Syawal. Data collection techniques, namely observation and documentation, are then processed using a percentage formula. The results of this study indicate an increase in literacy skills through letter ball games. It can be seen from the success of each cycle, cycle I first meeting was 46%, increased at the second meeting to 54% and increased to 63% at the third meeting. In the second meeting, the child's literacy ability was 69% at the second meeting, 74% at the second meeting, and 86% at the third meeting. From the results of the research in each cycle that was carried out, it can be concluded that the letter ball game can improve the literacy skills of Kindergarten B children